1998
DOI: 10.1007/bf02385954
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity on the Montenegrin Coast, Yugoslavia

Abstract: Environmental radioactivity has been investigated on the Montenegrin Coast (Yugoslavia). Radioactivity was measured on 14 beaches and 5 hinterland localities by a method of in situ gamma-spectrometry. At each measuring site two photon countings were performed in ground and above it. Specific activities of 4~ 232Th, 238U, 137Cs and corresponding exposure rates were then obtained from gamma-spectra and appropriate radiation field models. The results show a washing out effect of the sea-water: radioactivity level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
0
6
2
Order By: Relevance
“…U in this study is much higher than the reported world-wide data [8]. Upon comparing the results of 137 Cs with global data it was found that the obtained values of 137 Cs after contamination are far below the reported range investigated by many researcher around the world [9][10][11]. However, the range of 137 Cs concentrations observed in this study is significantly high relative to similar data reported from Libya 0.9 -1.7 Bq/kg [12].…”
Section: Radioativity Measurementcontrasting
confidence: 73%
See 1 more Smart Citation
“…U in this study is much higher than the reported world-wide data [8]. Upon comparing the results of 137 Cs with global data it was found that the obtained values of 137 Cs after contamination are far below the reported range investigated by many researcher around the world [9][10][11]. However, the range of 137 Cs concentrations observed in this study is significantly high relative to similar data reported from Libya 0.9 -1.7 Bq/kg [12].…”
Section: Radioativity Measurementcontrasting
confidence: 73%
“…235 U was detected in 9 samples out of 18 samples and ranged from 5.23 -104.160 with an average value of 23.199 ± 32.072 Bq/kg.Moreover , depleted uranium (DU) was investigated on the basis of the natural 235U/238U activity ratio that was determined to be 0.046 . Only if the obtained ratio is higher than the given value can the presence of DU be recorded [6][7][8][9][10][11][12][13]. DU was detected at 9 ut of 18 samples see Table 1.…”
Section: Radioativity Measurementmentioning
confidence: 99%
“…We can compare results of this radon survey with some results obtained in the winter season of 1994/1995, during an investigation of environmental radioactivity on the Montenegrin Coast (Vukotic et al, 1998). That investigation encompassed in situ measurements of external gamma exposure on the beaches and on their hinterlands, as well as radon and in situ gammaradiation measurements inside the hotels.…”
Section: Discussionmentioning
confidence: 90%
“…Although radon measurements in Montenegro started 10 y ago Vukotic et al, 1997Vukotic et al, , 1998Antovich et al, 2002), the first systematic long-term radon survey commenced in 2002, in the frame of the ongoing national radon program.…”
Section: Introductionmentioning
confidence: 99%
“…Although some previous investigations showed that, in general, sand and pebbles from Montenegrin beaches have a low content of uranium and thorium (Vukotic et al, 1998), these are the first systematic 226 Ra activity measurements in soil and sand samples from the settlements on the Montenegrin Coast (six municipalities: Herceg Novi, Kotor, Tivat, Budva, Bar and Ulcinj, which also include settlements: Sutomore, Petrovac, Sveti Stefan, Milocer, Igalo) which is a narrow strip of land, separated from the hinterland by mountain ranges that at some points rise up to 1700 m. It is up to 10 km wide and 100 km long by air, with a 293 km long coastline. The surface part of terrains is predominantly made of three types of soil: anthropogenized Mediterranean cambisols on flyshe, which is characteristic of the Herceg Novi, Tivat and Bar settlements; anthropogenized cambisols on calcareoussilicate rocks, present in Kotor and Ulcinj; alluvial and alluvial-diluvial calcareous gleyed and poorly saline soils, in the regions of Herceg Novi, Budva, Tivat and Bar.…”
Section: Ra Activity In Sand and Soil Samples From The Montenegrimentioning
confidence: 98%